A hundred years of Pacific halibut management in the context of global events and trends in fisheries management - Hutniczak, Barbara; Wilson, David T.; Stewart, Ian J.; Hicks, Allan C. (Frontiers in Marine Science, 2024)
The Convention for the Preservation of the Halibut Fisheries of the Northern Pacific Ocean, signed between Canada and the United States of America on 2 March 1923 and ratified on 21 October 1924, established the International Fisheries Commission, renamed in 1953 to the International Pacific Halibut Commission (IPHC). It was the first international agreement for joint management of a marine fishery resource and a major milestone for development of modern standards for marine conservation. The IPHC’s centennial year is an opportunity to celebrate a remarkable history of the Commission, but also reflect on challenges that shaped its mission. Born from alarms about overfishing during World War I, the Commission gradually gained authority to implement a wide range of conservation measures through established public confidence in its basis for decisions. This paper explores the evolution of management measures applied to Pacific halibut commercial fishing shaped not only by the changing stock conditions and growing demand for seafood, but also global events and trends in fisheries management. It examines the impact of rapid commercialization of fisheries driven by population growth and technological improvements, establishment of exclusive economic zones and altered access to fishing grounds, and adoption of Agenda 21, which highlighted the importance of balancing environmental, economic, and social aspects in fisheries management. It concludes by discussing the lessons learned over the past century and their implications for future fisheries management, emphasizing the importance of international cooperation, adaptive strategies, and science-based policies in sustaining transboundary fish stocks like the Pacific halibut.